Situs Sakral Sebagai Pusat Kosmos: Analisis Kepercayaan Masyarakat Kampung Pitu, Nglanggeran, Gunung Kidul Dalam Perspektif Teori Sakral-Profan Mircea Eliade - Alfarauq, Farkhan Abdurochim; Abrori, Ahmad; Arif, Muhamad; Zaimudin (PURBAWIDYA, 2025)
This research aims to understand how the beliefs and sacred sites of the Pitu Village community are analyzed through Mircea Eliade's theory. This study is qualitative, utilizing mixed interviews, observation, and documentation. The results indicate that the concept of the sacred in the beliefs of the Pitu Village community has been present since the community was formed. The Kinah Gadung Wulung tree and Telogo Guyangan become hierophanies. Sacred rituals are focused on the pond, which is believed to be a place of efficacy. The cosmos manifested in the Pitu Village community also serves as the axis mundi for the community, located at Telaga Guyangan. Ancestral teachings serve as a blueprint to protect them from chaos, including the prohibition on the number of family cards, which must total seven, forming the basis for the village structure and representing an imago mundi. Pitu Village is distinct in its presence of ancestors and elders as elements of the Sacred, receiving special rituals and becoming axis mundi takes the form of a human because in the life of the Kampung Pitu community, they must firmly hold on to their teachings and seek advice when they want to carry out something.